Government Position in Religious Authority Contestation in Indonesia: Reviewing the Government Authority in Determining the Beginning of Islamic Months - Musonnif, Ahmad; Mahardika, Ahmad Gelora; Maratus, Nuril Farida; Muttaqin, Muhammad Ngizzul (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
This article aims to examine the government's efforts and effectiveness in establishing itself as the sole religious authority in determining the beginning of the Islamic month. This qualitative study utilizes data from news sources, official decisions, and government activities related to setting the Islamic calendar, as well as fatwas from the Indonesian Ulema Council. Additionally, it presents the community's response, particularly from religious organizations, to the government's role in this matter. Drawing on Ismail Fajrie Alatas's theory of religious authority, which suggests that religious authority is shaped by a connection to the prophetic tradition and by fostering intellectual and emotional bonds with the community through service and outreach, the study finds that the government's effort to become the exclusive religious authority has encountered challenges. While the government aligns with the prophetic tradition by employing the ru'yah method (crescent sighting), based on authentic hadiths and followed by the majority of Muslims, the lack of intellectual and emotional connection with certain groups—such as Muhammadiyah and other religious congregations—leads them to resist the government's stance. In contrast, communities with closer intellectual and emotional ties to the government, like Nahdlatul Ulama, are more likely to align with its decisions. In the complex landscape of religious authority in Indonesia, the government navigates various roles, including tolerance, intervention, negotiation, and accommodation.